LEADERSHIP AND SCHOOL GOVERNANCE IN REALIZING QUALITY VOCATIONAL EDUCATION - Aprianto; Yayat Nurhidayat (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2026)
This study aims to analyze the role of school leadership and governance in achieving quality vocational education at SMK Negeri 13 Bandung. The research focuses on how school leadership mobilizes organizational resources, fosters a culture of quality, and implements effective governance practices to improve educational services and graduate outcomes. A qualitative approach with a descriptive analytical method was employed. Data were collected through participant observation, in-depth interviews with key stakeholders, including the principal, teachers, administrative staff, students, parents, and industry partners, as well as document analysis. The findings reveal that the principal’s leadership plays a strategic role in establishing a shared vision, strengthening organizational commitment, and encouraging active participation among school members in achieving educational goals. School governance practices, supported by systematic planning, implementation, monitoring, and evaluation, contribute significantly to the effectiveness of educational services and institutional performance. The major challenges identified were not related to financial resources, facilities, or technical competencies, but rather to organizational culture, particularly resistance to change, limited self-initiative, and varying levels of quality awareness among school members. Despite these challenges, effective leadership and governance have positively impacted graduate quality, employment absorption rates, academic achievement, and stakeholder trust. The study concludes that strong leadership and sound governance are critical factors in promoting quality vocational education and sustaining institutional excellence.